2013
DOI: 10.1371/journal.pone.0059761
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Specificity of Human Galectin-8C Domain Interactions with Its Glycan Ligands Based on Molecular Dynamics Simulations

Abstract: Human Galectin-8 (Gal-8) is a member of the galectin family which shares an affinity for β-galactosides. The tandem-repeat Gal-8 consists of a N- and a C-terminal carbohydrate recognition domain (N- and C-CRD) joined by a linker peptide of various length. Despite their structural similarity both CRDs recognize different oligosaccharides. While the molecular requirements of the N-CRD for high binding affinity to sulfated and sialylated glycans have recently been elucidated by crystallographic studies of complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
5
21
0
Order By: Relevance
“…Carbohydrate-binding characteristics of galectins involve (i) the array of glycan ligands; (ii) the architecture, dynamics, and binding sites of CRDs; and (iii) the topological display of glycans. It has been suggested that differences in the amino acid properties of galectins are responsible for the different binding of glycans to the CRDs, since the 3D structure of the galectin CRDs have an almost identical fold, while their amino acid sequence identity is rather low ( 18 20 ). For example, the CRD of galectin-3 is 30–40% identical with galectins 4–10 and 20–25% identical with galectin-1 and -2 ( 21 – 23 ).…”
Section: Galectin-3 and Its Key Structure To Function Relationshipsmentioning
confidence: 99%
“…Carbohydrate-binding characteristics of galectins involve (i) the array of glycan ligands; (ii) the architecture, dynamics, and binding sites of CRDs; and (iii) the topological display of glycans. It has been suggested that differences in the amino acid properties of galectins are responsible for the different binding of glycans to the CRDs, since the 3D structure of the galectin CRDs have an almost identical fold, while their amino acid sequence identity is rather low ( 18 20 ). For example, the CRD of galectin-3 is 30–40% identical with galectins 4–10 and 20–25% identical with galectin-1 and -2 ( 21 – 23 ).…”
Section: Galectin-3 and Its Key Structure To Function Relationshipsmentioning
confidence: 99%
“…galectins). 34 The galactose on hydroxylysine (native form) shows an average of 0.69, 0.47 and 0.36 H-bonds, respectively, at position 3, 4 and 6 (Fig. 2, panel B).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 97%
“…In fact, each member of the galectin family exhibits preferences in different glycan binding [ 10 ], which could explain their differences in biological and pathophysiological functions and the wide range of identified receptors on cell surfaces [ 2 , 11 ]. In particular, the tandem repeat type galectins, galectin-8 and -9, carry two CRDs (N and C terminal) that, despite their structural similarity, recognize different oligosaccharides (i.e., sulfated or sialylated glycans or biantennary oligosaccharide) due to different affinity [ 12 , 13 , 14 ]. Moreover, the modification of the short peptide linker of tandem repeat-type galectins could also modify their biological functions [ 15 ].…”
Section: Biological and Pathophysiological Functions Of Galectinsmentioning
confidence: 99%